Aromaterapi Lavender dapat Menurunkan Intensitas Nyeri Perineum pada Ibu Post Partum - Wiwin Widayani (Alma Ata University Press, 2016)
Perineals pain affects woman ability to mobilize so that it can cause complications such as post-partum haemoragik. Trauma to the perineum also cause discomfort and dyspareunia, therefore, perineal pain management is important. Currently the handling used to relieve pain is complementary therapy aromatherapy with essential oils of lavender, because lavender has the properties of anticonvulsant, antidepressant, anxiolytic, and also soothing. Aromatherapy stimulates the hypothalamus to secrete chemical mediators that serve as pain relievers and give rise to feelings of happiness. The purpose of this study was to determine the effect of lavender aromatherapy to the perineal pain intensity in post partum women. This study is a quasy experiment pre and post non random control in postpartum women at Bidan Praktik Mandiri in Bandung. Sampling this study using consecutive sampling technique. The data taken using the instrument in the adaptation of a Visual Analog Scale (VAS) and analyzed by using the wilcoxon signed rank test. The result is there was a decrease in pain intensity before and after the administration of inhaled lavender aromatherapy (Z=-3.77) with p-value 0.001. Lavender aromatherapy can be a complementary alternative therapy to reduce pain in postpartum women but more research necessary is needed with more respondents.